THE ROLE OF MEDIA ARTS INTHE DEVELOPMENT OF TOURISM AND ECONOMY OF REGIONS / Роль медиаискусств в развитии туризма и экономики регионов - BELOZEROVA Y.M. / БЕЛОЗЕРОВА Ю.М. (Наука телевидения, 2017)
The article discusses the relationship between tourism and cinema. Despite the tense international situation, tourism continues to maintain strong growth at 4-5% a year, above the average growth of the economies of the leading countries of the world. But the film industry shows quite high growth rates. By the examples of different movies, the author illustrates the development of cinema tourism, a new kind of recreation which allows to travel to places of shooting locations, where famous movie stars had been filmed.